Characteristics and controlling factors of the Upper Permian Dalong Formation in northwestern Sichuan Basin, China - Wang, Lu; Guan, Xiaodong; Wang, Jianyong; Sun, Zuoyu; Xu, Huiyuan (Frontiers in Earth Science, 2023)
Recently, many oil companies have made significant breakthroughs to the exploration of Permian shale oil and gas in the Sichuan Basin, China. It has been generally accepted that the Permian shale is an important target for shale oil and gas exploration. But there are still some questions need to clarify, especially the mechanism of forming the excellent Permian source rock. In order to precisely predict the distribution of potential excellent source rocks of shale oil and gas, it is necessary to reveal the forming process and mechanism of high-quality source rocks, such as the Dalong Formation in the Scihuan Basin. In this study, 17 samples were collected from the Dalong Formation in Longfeng Quarry, Northwest Guangyuan City, Sichuan Province. The lithofacies, organic geochemistry, and pyrolysis of these samples were analyzed to evaluate the main factors controlling their formation. In particular, the influences of hydrothermal and paleoenvironment factors on the accumulation of organic matter were analyzed. The total organic carbon (TOC) content of the samples, which ranges from 0.05% to 12.21%, is closely related to the lithology. High TOC has been generally observed in rock intervals developed in a deep-water sedimentary environment, including siliceous rock, dark shale, and siliceous shale. In addition the thickness of the rock interval is also related to the TOC. The peak pyrolysis temperature of the samples ranges from 444°C to 462°C, indicating a mature stage. Thin-section observation, combined with the results of previous studies, has confirmed that the source of the organic matter is mainly marine phytoplankton, such as algae, radiolarians, ostracods, and other marine organisms, which comsist of these high-quality source rocks. The ratio of trace elements, such as Ni/Co, V/Cr, U/Th, and V/(V + Ni) indicates that high-quality source rocks are mainly formed in anoxic closed environments. The hydrothermal activity of submarine volcanoes provided many nutrients and compounds, resulting biological prosperity and improving primary productivity. This is simultaneously conducive to the formation of anoxic environments and the preservation of organic matter.